KONSERVASI DAN PEMANFAATAN LAHAN SEBAGAI UPAYA MENJAGA KELESTARIAN ALAM PERSPEKTIF HADIS NABI - Nurfauzi, Deril; Muthi'ah, Anisatun; Sakur, Lukman Zain M. (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
This research is motivated by the increasing level of natural destructions. Many people think that the convenience of technology in this modern era will be a way to get convenience in life in this world. But in reality, there are many impacts of natural damage due to the rapid development of technology today. The universe basically has the most important role for living things. Because humans, plants, the universe and everything in it are creatures created by Allah SWT whose preservation must be protected. Departing from the background above, researchers are interested in researching more deeply about